Komunikasi Matematis: Profil Siswa dalam Menyelesaikan Masalah Kontekstual Secara Kolaboratif - Mulyani, Andini Endah Sri; Irawan, Wahyu Henky; Sujarwo, Imam; Abdussakir, Abdussakir; Turmudi, Turmudi (Universitas Islam Negeri Sayyid Ali Rahmatullah Tulungagung, 2024)
The development of the 21st century demands that students not only have the ability to think critically and creatively, but also communication skills, especially in mathematics learning. However, various studies show that students still have difficulty communicating their mathematical ideas, both verbally and in writing, especially when working in groups and facing contextual problems. The purpose of this study is to describe the mathematical communication profile of students in solving contextual problems collaboratively reviewed based on high, medium, and low self-efficacy. A qualitative approach with an exploratory research type is used in this study. The subject of the study is a student of class XI MAN 2 Malang. The research data were obtained through the results of the Contextual Problem Solving Task (TPMK) and interviews. Data analysis was carried out by the triangulation method. The results showed that students with high self-efficacy tended to communicate their mathematical ideas orally. Students with self-efficacy showed balanced verbal and written communication but were less consistent in explaining mathematical models and operations, while students with low self-efficacy were more dominant in written communication.